STRATEGI PEMBELAJARAN MENGATASI KESULITAN ANAK SEKOLAH DASAR DALAM MENGERJAKAN SOAL CERITA MATEMATIKA - Maya Damayanti (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2022)
Learning Strategies in Overcoming Difficulties of Elementary School Children Working About Mathematics Story Problems. The problem that often occurs in learning mathematics in elementary schools is the difficulty of working on word problems. For this reason, this study aims to find out the appropriate learning strategies to overcome these problems. The difficulty in working on math word problems is due to students' reasoning that has not been honed and learning strategies that are less effective in reaching all student characteristics. Therefore, an effective learning method is needed, one of which is by implementing a learning strategy in the form of a problem-based learning model. This learning model is neko77 an effective approach so that students are able to improve reasoning about problems in everyday life that can be solved with material, concepts, and knowledge from a field of study. In learning mathematics, this learning model can familiarize students with solving problems in everyday life with mathematical concepts and operations. With this learning strategy, the learning process can run effectively and support an active class atmosphere so that it can support student learning outcomes.